1965
DOI: 10.1099/00221287-39-2-253
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of the Virus of Bovine Malignant Catarrhal Fever in East Africa

Abstract: SUMMARYA strain of bovine malignant catarrhal fever virus (MCF) recovered from the blood of a blue wildebeest was developed by passage in vitro to a stage where it could be propagated serially in primary thyroid cell cultures by inoculation of cell-free fluids. Released virus titres ranged from 103.8 to 105.8 50% tissue culture infectious doses/ml. This virus still caused fatal disease when inoculated to cattle, and was neutralized by antibody that appeared in the sera of cattle recovering from experimental in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

1966
1966
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 32 publications
(14 reference statements)
1
21
0
Order By: Relevance
“…BMV is therefore identified as another bovine member of the family of herpesviruses. Like other bovine herpesviruses, it produces syncytia and intranuclear inclusions in cultured cells, It resembles IBR virus (Armstrong,Pereira & Andrewes,19Sl), but differs from most lines of MCF virus (Plowright, Macadam & Armstrong, 1965) in its relative ease of cultivation and its release in significant amount from infected cells into the culture fluid. The serological reactions of BMV separate it clearly from these and other herpesviruses, with the exception of the Allerton prototype strain of the group I1 viruses of lumpy skin disease (Alexander et al 1957), from which it cannot be distinguished in standard neutralization and agar-precipitation tests.…”
Section: Discussionmentioning
confidence: 99%
“…BMV is therefore identified as another bovine member of the family of herpesviruses. Like other bovine herpesviruses, it produces syncytia and intranuclear inclusions in cultured cells, It resembles IBR virus (Armstrong,Pereira & Andrewes,19Sl), but differs from most lines of MCF virus (Plowright, Macadam & Armstrong, 1965) in its relative ease of cultivation and its release in significant amount from infected cells into the culture fluid. The serological reactions of BMV separate it clearly from these and other herpesviruses, with the exception of the Allerton prototype strain of the group I1 viruses of lumpy skin disease (Alexander et al 1957), from which it cannot be distinguished in standard neutralization and agar-precipitation tests.…”
Section: Discussionmentioning
confidence: 99%
“…Plowright et al (1963), Plowright (1968, Castro et al (1982) have found big syncytia and inclusion bodies in bovine embryonic testis cells and bovine foetal kidney of isolates originating from an Indian gaur and Greater kudu with typical clinical signs of MCF. We have observed growing of infected MDBK cell culture with samples from organ suspensions from gaur (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mammillitis and skin disease are induced by BHV-2 (Martin et al, 1966). Antelope-associated bovine malignant catarrhal fever (MCF) in Africa was proven to be caused by BHV-3 (Plowright et al, 1960(Plowright et al, , 1965. Herpesviruses were isolated from lungs of sheep (Malmquist et al, 1972;De Villiers et al, 1975), and these isolates were later categorized as BHV-5 by De Villiers (1979).…”
Section: Introductionmentioning
confidence: 99%